SUSTAINABLE GROWTH OF THE MALAYSIAN DEFENCE INDUSTRY : ISSUE AND CHALLENGES - Mohd Syahrizal Bin Basri (Thesis, 2023)
The study aimed to explore the obstacles and concerns encoutered by Malaysian defence industry in achieving long term growth that is sustainable. The purpose of this study is to determine the issues and challenges for sustainable growth of Malaysian defence industry and provide some recommendations to ensure the growth of Malaysian defence industry.